A sulfur bond self-healing material and a preparation method and application thereof
Patent Information
- Application Number
- CN202610824842.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-16
AI Technical Summary
然而,该聚合物体系的力学性能有限,断裂伸长率仅为66%,且自修复能力较为一般,在室温下修复24小时后极限抗拉强度的恢复率仅为83%
[0046]1、本发明以含羟基苯并二唑衍生物为原料,首先将其与带有长烷基侧链的溴代甲基丙烯酸酯在碱性条件下发生亲核取代反应,制得含苯并二唑基团的长侧链甲基丙烯酸酯单体,再在引发剂作用下通过自由基聚合,实现目标硫键自愈合材料的高效合成。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a self-healing sulfur bond material, its preparation method and application, belonging to the field of organic synthesis technology. Background Technology
[0002] A sulfur bond is a non-covalent interaction between chalcogenides (S, Se, Te) and Lewis bases. Because chalcogenides generate a positive electrostatic potential region along the covalent bond direction, they tend to interact with electron donors at linear bond angles, thus giving sulfur bonds a unique directionality. Based on this property, sulfur bonds have been widely used in drug design, crystal engineering, anion recognition and transport, and catalysis. Compared to hydrogen bonds, sulfur bonds exhibit higher directionality, stronger resistance to water interference, and tunable interaction strength, making them highly attractive in the field of functional materials.
[0003] Tuten et al. from Queensland University of Technology in Australia first demonstrated the concept of sulfur bond-driven self-healing (Angew. Chem. Int. Ed. 2024, 63, e202404474). However, the mechanical properties of this polymer system are limited, with an elongation at break of only 66%, and its self-healing ability is relatively weak, recovering only 83% of its ultimate tensile strength after 24 hours of repair at room temperature. These limitations severely restrict its practical application and highlight the urgent need for further molecular design and optimization.
[0004] Therefore, there is an urgent need to construct self-healing materials with disulfide bonds and novel frameworks, thereby endowing the materials with high elongation at break and achieving rapid self-healing. To this end, this invention is proposed. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a self-healing sulfur bond material, its preparation method, and its applications. This invention uses a hydroxybenzodiazole derivative as a raw material. First, it reacts the derivative with a bromomethacrylate containing a long alkyl side chain under alkaline conditions to obtain a benzodiazole-containing long-side-chain methacrylate monomer. Then, under the action of an initiator, free radical polymerization is used to achieve the efficient synthesis of the target self-healing sulfur bond material. The self-healing sulfur bond material synthesized by this invention exhibits an elongation at break greater than 10,000% and can achieve complete self-healing within 2 hours at room temperature.
[0006] The technical solution of the present invention is as follows: A method for preparing a self-healing material with disulfide bonds includes the following steps: (1) In solvent A, under the action of alkali, compound I is reacted with undecyl 11-bromomethacrylate II to obtain monomer III; ; In compounds of formula I and monomers of formula III, X is Se or O; (2) In solvent B, under the action of an initiator, monomer III and polyethylene glycol dimethacrylate undergo free radical polymerization to obtain a sulfur bond self-healing material.
[0007] According to a preferred embodiment of the present invention, the solvent A in step (1) is N,N-dimethylformamide or toluene; the volume ratio of the solvent A to the molar number of the compound of formula I is 20-30 mL: 1 mmol.
[0008] According to a preferred embodiment of the present invention, the alkali in step (1) is potassium carbonate, potassium hydroxide or sodium hydroxide, and the molar ratio of the alkali to the compound of formula I is 1-1.2:1.
[0009] According to a preferred embodiment of the present invention, the molar ratio of 11-bromomethacrylate undecyl ester II to the compound of formula I in step (1) is 1.05-1.2:1.
[0010] According to a preferred embodiment of the present invention, the temperature of the reaction in step (1) is 80-90°C, the reaction time is 8-12 h, and the reaction is carried out under an argon atmosphere.
[0011] According to a preferred embodiment of the present invention, after the reaction in step (1) is completed, the post-processing steps of the resulting reaction solution are as follows: the solvent is removed from the resulting reaction solution, and the crude product is purified by silica gel column chromatography to obtain monomer III; the eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 3:1.
[0012] According to a preferred embodiment of the present invention, when X in step (1) is Se, the compound of formula I has the structure shown in formula I-1: ; The compound shown in Formula I-1 was prepared by the following method: In solvent C, 4-amino-3-nitrophenol IV was hydrogenated under the catalysis of palladium on carbon to obtain 3,4-diaminophenol V; in solvent D, 3,4-diaminophenol V was subjected to an oxidative cyclization reaction with SeO2 to obtain compound I-1. .
[0013] Preferably, in the preparation of the compound shown in Formula I-1, the solvent C is methanol, ethanol or isopropanol; the volume ratio of the solvent C to the molar number of 4-amino-3-nitrophenol IV is 5-10 mL: 1 mmol.
[0014] Preferably, in the preparation of the compound shown in Formula I-1, the mass fraction of palladium in the palladium-on-carbon catalyst is 10%, and the mass of the palladium-on-carbon catalyst is 5-15% of the mass of 4-amino-3-nitrophenol IV.
[0015] Preferably, in the preparation of the compound shown in Formula I-1, the pressure of the hydrogenation reaction is 0.1-0.2 MPa, and the time of the hydrogenation reaction is 6-10 h.
[0016] Preferably, in the preparation of the compound shown in Formula I-1, after the hydrogenation reaction is completed, the post-treatment steps of the resulting reaction solution are as follows: the resulting reaction solution is filtered through diatomaceous earth under an argon atmosphere, and the solvent is removed from the filtrate to obtain 3,4-diaminophenol V.
[0017] Preferably, in the preparation of the compound shown in Formula I-1, the solvent D is ethanol or isopropanol; the volume ratio of the solvent D to the molar number of 4-amino-3-nitrophenol IV is 5-15 mL: 1 mmol.
[0018] Preferably, in the preparation of the compound shown in Formula I-1, the molar ratio of SeO2 to 4-amino-3-nitrophenol IV is 1-1.05:1.
[0019] Preferably, in the preparation of the compound shown in Formula I-1, the temperature of the oxidative cyclization reaction is 75-83°C, the time of the oxidative cyclization reaction is 8-12 h, and the oxidative cyclization reaction is carried out under an argon atmosphere.
[0020] Preferably, in the preparation of the compound shown in Formula I-1, after the oxidative cyclization reaction is completed, the post-treatment steps of the resulting reaction solution are as follows: the solvent is removed from the resulting reaction solution, and the crude product is purified by silica gel column chromatography to obtain the compound shown in Formula I-1; the eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 2:1.
[0021] According to a preferred embodiment of the present invention, when X is O in step (1), the compound of formula I has the structure shown in formula I-2: ; The compound shown in Formula I-2 was prepared by the following method: (i) At 0-5°C, an aqueous solution of NaClO was added dropwise to an ethanol solution containing potassium hydroxide and 2-nitro-4-methoxyaniline VI to carry out an oxidative cyclization reaction to obtain compound VII; in solvent E, compound VII was reacted with triethyl phosphite to obtain compound VIII.
[0022] (ii) At -35 to -30°C, BBr3 was added dropwise to a 1,2-dichloroethane solution of compound VIII, stirred until homogeneous, and then reacted to obtain the compound shown in formula I-2.
[0023] Preferably, in the preparation of the compound shown in Formula I-2, the mass fraction of the NaClO aqueous solution in step (i) is 5-10%; the molar ratio of NaClO to 2-nitro-4-methoxyaniline VI is 1.05-1.2:1.
[0024] Preferably, in the preparation of the compound shown in Formula I-2, the molar ratio of potassium hydroxide to 2-nitro-4-methoxyaniline VI in step (i) is 1.05-1.2:1.
[0025] Preferably, in the preparation of the compound shown in Formula I-2, the concentration of 2-nitro-4-methoxyaniline VI in the ethanol solution containing potassium hydroxide and 2-nitro-4-methoxyaniline VI in step (i) is 0.5-2 mmol / mL.
[0026] Preferably, in the preparation of the compound shown in Formula I-2, the temperature of the oxidative cyclization reaction in step (i) is 0-5℃ and the reaction time is 20-30 min; after the reaction is completed, the post-processing steps are as follows: filter the obtained reaction solution, wash the precipitate obtained by filtration with water, and dry the solid obtained by washing under vacuum at 70-80℃ for 10-15 h to obtain the compound of Formula VII.
[0027] Preferably, in the preparation of the compound shown in Formula I-2, the solvent E in step (i) is tetrahydrofuran; the volume ratio of the solvent E to the molar number of the compound of Formula VII is 0.5-2 mL:1 mmol.
[0028] Preferably, in the preparation of the compound shown in Formula I-2, the molar ratio of triethyl phosphite to the compound of Formula VII in step (i) is 2-2.2:1.
[0029] Preferably, in the preparation of the compound shown in Formula I-2, the reaction temperature of the compound of Formula VII with triethyl phosphite in step (i) is 55-65°C, and the reaction time is 5-10 h; the reaction is carried out under a nitrogen atmosphere.
[0030] Preferably, in the preparation of the compound shown in Formula I-2, after the reaction of the compound of Formula VII with triethyl phosphite in step (i) is completed, the post-treatment steps of the resulting reaction solution are as follows: the resulting reaction solution is naturally cooled to room temperature, diluted with water, and then the resulting mixture is extracted with n-hexane. The resulting organic phase is washed with saturated brine, dried with anhydrous MgSO4 to remove the solvent, and a crude product is obtained. The crude product is purified by silica gel column chromatography to obtain the compound of Formula VIII. The eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 20:1.
[0031] Preferably, in the preparation of the compound shown in Formula I-2, the molar ratio of BBr3 to the compound of Formula VIII in step (ii) is 4-4.2:1.
[0032] Preferably, in the preparation of the compound shown in Formula I-2, the concentration of the compound of Formula VIII in the 1,2-dichloroethane solution of the compound of Formula VIII in step (ii) is 0.1-0.3 mmol / L.
[0033] Preferably, in the preparation of the compound shown in Formula I-2, the stirring temperature in step (ii) is -35~-30℃, and the stirring time is 20-30min.
[0034] Preferably, in the preparation of the compound shown in Formula I-2, the reaction temperature in step (ii) is 80-85°C and the reaction time is 20-30 h.
[0035] Preferably, in the preparation of the compound shown in Formula I-2, after the reaction in step (ii) is completed, the post-treatment steps of the obtained reaction solution are as follows: the obtained reaction solution is cooled to -78°C, and methanol is added to quench the reaction; the solvent is removed from the obtained mixture, and the crude product is purified by silica gel column chromatography to obtain the compound shown in Formula I-2. The eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 10:1.
[0036] According to a preferred embodiment of the present invention, solvent B in step (2) is N,N-dimethylformamide or toluene; the volume ratio of solvent B to the molar number of monomer III is 0.5-1.5 mL:1 mmol.
[0037] According to a preferred embodiment of the present invention, the initiator in step (2) is azobisisobutyronitrile (AIBN) or benzoyl peroxide (BPO); the molar ratio of the initiator to monomer III is 0.01-0.05:1.
[0038] According to a preferred embodiment of the present invention, the number average molecular weight of the polyethylene glycol dimethacrylate in step (2) is 200-400 g / mol.
[0039] According to a preferred embodiment of the present invention, the molar ratio of polyethylene glycol dimethacrylate to monomer III in step (2) is 0-0.2:1.
[0040] According to a preferred embodiment of the present invention, the temperature of the free radical polymerization reaction in step (2) is 65-75°C, the time of the free radical polymerization reaction is 20-30 h, and the free radical polymerization reaction is carried out under a nitrogen atmosphere.
[0041] According to a preferred embodiment of the present invention, after the free radical polymerization reaction in step (2) is completed, the post-treatment steps are as follows: the obtained reaction mixture is naturally cooled to room temperature, water is added, and then cured at 70-80°C for 10-15 hours under nitrogen protection to obtain a sulfur bond self-healing material; the ratio of the volume of water added to the molar number of monomer III is 8-12 mL: 1 mmol.
[0042] The present invention also provides a self-healing sulfur bond material, which is prepared by the above preparation method.
[0043] According to the present invention, the above-mentioned sulfur bond self-healing material is suitable for preparing a variety of high-performance materials, including: fatigue-resistant and impact-resistant composite materials, biomedical implants, stretchable and deformation-resistant flexible electronic devices, and self-healing coatings with surface protection and durability enhancement functions.
[0044] In this invention, room temperature has a commonly known meaning, referring to 25±5℃.
[0045] The technical features and beneficial effects of this invention are as follows:
[0046] 1. This invention uses hydroxybenzodiazole derivatives as raw materials. First, it reacts with bromomethacrylates with long alkyl side chains under alkaline conditions to undergo a nucleophilic substitution reaction, thereby obtaining long-side-chain methacrylate monomers containing benzodiazole groups. Then, under the action of an initiator, it achieves efficient synthesis of the target sulfur bond self-healing material through free radical polymerization.
[0047] 2. This invention can construct a type of dynamic sulfur bond polymer network with high conversion rate from inexpensive raw materials. Compared with known dynamic sulfur bond networks, it exhibits higher self-healing efficiency and better elongation at break. Attached Figure Description
[0048] Figure 1 Photographs of the self-healing sulfur bond material prepared in Example 1 after damage (a), healing (b), healing before stretching (c), and healing after stretching (d).
[0049] Figure 2 The stress-strain tensile curves are for the disulfide bond self-healing materials prepared in Examples 1 and 2.
[0050] Figure 3 The stress-strain tensile curves of the disulfide bond self-healing material prepared in Example 1 after self-healing in natural environment and in water are shown. Detailed Implementation
[0051] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0052] The palladium on carbon used in the examples has a palladium mass fraction of 10%.
[0053] Example 1
[0054] Synthesis of Se-polymer, a self-healing material for sulfur bonds
[0055] The reaction route is as follows:
[0056] The specific steps are as follows: (1) Synthesis of intermediate V: 4-amino-3-nitrophenol IV (6.5 mmol, 1.00 g) and palladium on carbon (0.10 g) were added to methanol (55 mL) under an argon atmosphere; the reaction flask was purged with hydrogen twice and then stirred for 8 hours under a hydrogen atmosphere at room temperature with a hydrogen pressure of 0.1 MPa; after the reaction was completed, the resulting reaction solution was filtered through diatomaceous earth under an argon atmosphere, and the solvent was removed by vacuum distillation of the filtrate to obtain 3,4-diaminophenol V; (2) Synthesis of compound I-1: Under an argon atmosphere, 3,4-diaminophenol V obtained in step (1) was added to 60 mL of ethanol, and then SeO2 (0.72 g, 6.5 mmol) was added. The mixture was stirred at 80 °C under an argon atmosphere for 10 hours. After the reaction was completed, the solvent was removed from the reaction solution, and the crude product was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 2:1, v / v) to obtain compound I-1. The total yield of the two steps was 71%. (3) Synthesis of monomer III: Under an argon atmosphere, 11-bromomethacrylate undecyl ester II (1.06 g, 3.32 mmol) was added to 80 mL of DMF, followed by potassium carbonate (0.42 g, 3.0 mmol) and compound I-1 (0.60 g, 3.0 mmol). The mixture was stirred at 85 °C under an argon atmosphere for 10 hours. After the reaction was completed, the solvent was removed from the resulting reaction solution, and the crude product was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 3:1, v / v) to obtain monomer III with a yield of 68%.
[0057] The characterization data for monomer III are as follows: 1HNMR (400 MHz, CDCl3): δ 7.64 (d, J = 9.6 Hz, 1H), 7.20 (dd, J = 9.6,2.5 Hz, 1H), 6.98 (d, J = 2.4 Hz, 1H), 6.09 (t, J = 1.4 Hz, 1H), 5.55-5.53(m, 1H), 4.14 (t, J = 6.7 Hz, 2H), 4.03 (t, J = 6.5 Hz, 2H), 1.94 (d, J =1.4 Hz, 3H), 1.85 (dt, J = 14.7, 6.7 Hz, 2H), 1.70-1.63 (m, 2H), 1.49 (dq, J= 9.4, 6.8 Hz, 2H), 1.39-1.30 (m, 12H); 13 CNMR (101 MHz, CDCl3): δ 167.57, 160.94, 136.56, 126.70, 125.12,123.15, 99.19, 68.57, 64.82, 29.49, 29.47, 29.31, 29.22, 28.84, 28.59, 26.03,25.96, 18.32; HRMS (ESI+) exact mass calculated for [M+Na] + (C 21 H 30 N2O3SeNa + ) requires m / z 461.1314, found m / z 461.1319.
[0058] (4) Synthesis of self-healing sulfur bond material Se-polymer: Monomer III (2.0 mmol) was mixed with DMF (2 mL) and homogenized by ultrasonic treatment; the resulting solution was subjected to freezing-vacuuming-thawing cycle degassing, and the above degassing steps were repeated three times; after degassing, AIBN (0.05 mmol) was added to the above solution, and the reaction was stirred at 70 °C for 24 hours under nitrogen atmosphere; after the reaction was completed, the resulting reaction solution was naturally cooled to room temperature, 20 mL of water was added and stirred evenly, the resulting mixture was placed in a Teflon mold, and cured at 80 °C for 12 hours in a vacuum oven under nitrogen protection to obtain self-healing sulfur bond material Se-polymer.
[0059] The characterization data of the obtained sulfur bond self-healing material Se-polymer are as follows: 1 HNMR (400 MHz, CDCl3): δ 7.58 (d, J = 9.6 Hz, 1H), 7.13 (dd, J = 9.7,2.4 Hz, 1H), 6.92 (d, J = 2.6 Hz, 1H), 4.05-3.80 (m, 4H), 1.81 (h, J = 7.2Hz, 3H), 1.58 (s, 2H), 1.44 (t, J = 7.6 Hz, 2H), 1.36-1.23 (m, 12H), 1.02-0.83 (m, 2H); SEC: Mn=34000g / mol; Mw=98000g / mol; Ð=2.88.
[0060] Example 2 Synthesis of CL-Se-polymer, a self-healing material for sulfur bonds (1) Monomer III was prepared according to the method of Example 1; (2) Synthesis of CL-Se-polymer, a self-healing material for sulfur bonds: Monomer III (2.0 mmol), polyethylene glycol dimethacrylate (0.2 mmol, number average molecular weight Mn of 200) and DMF (2 mL) were mixed and homogenized by ultrasonic treatment; the resulting solution was degassed by freezing-vacuuming-thawing cycle, and the above degaussing steps were repeated three times; after degaussing, AIBN (0.055 mmol) was added to the above solution, and the mixture was stirred at 70 °C for 24 hours under nitrogen atmosphere; the resulting reaction solution was then naturally cooled to room temperature, 20 mL of water was added and stirred evenly, the resulting mixture was placed in a Teflon mold and cured at 80 °C for 12 hours in a vacuum oven under nitrogen protection to obtain the CL-Se-polymer, a self-healing material for sulfur bonds.
[0061] The characterization data of the obtained sulfur bond self-healing material CL-Se-polymer are as follows: 1 HNMR (400 MHz, CDCl3): δ 7.58 (d, J = 9.7 Hz, 1H), 7.13 (d, J = 9.7Hz, 1H), 6.92 (s, 1H), 4.22-3.51 (m, 5H), 2.01-0.71 (m, 27H).
[0062] Example 3 Synthesis of O-polymer, a self-healing material for disulfide bonds
[0063] The reaction route is as follows:
[0064] (1) Synthesis of intermediate VII: At 0°C, 400 mL of NaClO aqueous solution (6% by mass) was added dropwise (2 drops / s) to 255 mL of ethanol solution containing potassium hydroxide (18.00 g) and 2-nitro-4-methoxyaniline VI (0.30 mol). After the addition was complete, the mixture was stirred at 0°C for 20 minutes. After stirring, the reaction solution was filtered, the precipitate was washed with water, and the solid obtained was vacuum dried at 75°C for 12 h to obtain intermediate VII, which is a bright yellow solid. This product is unstable in air and should be used immediately after preparation.
[0065] (2) Synthesis of intermediate VIII: The crude product of intermediate VII (0.11 mol) was dissolved in THF (80 mL), and nitrogen was bubbled through the solution for 15 minutes under stirring. Triethyl phosphite (0.23 mol) was added dropwise to the resulting solution (dropping rate 2 drops / s). The mixture was stirred at 60 °C for 7 hours. During this period, the color of the mixture gradually darkened and the raw material was completely consumed (TLC monitoring). After the reaction was completed, the mixture was naturally cooled to room temperature, diluted with water (350 mL), extracted with 500 mL of n-hexane, and the resulting organic phase was washed with saturated brine, dried with anhydrous MgSO4, and the solvent was removed by vacuum distillation to obtain the crude product. The crude product was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 20:1, v / v) to obtain intermediate VIII.
[0066] (3) Synthesis of compound I-2: BBr3 (93.2 mmol) was added dropwise (2 drops / s) to a DCE solution (100 mL) of intermediate VIII (23.3 mmol) at -30 °C; the resulting reaction mixture was stirred at -30 °C for 20 minutes, and then stirred at 80 °C for 24 hours until TLC analysis confirmed that the reaction was complete; the reaction system was cooled to -78 °C, and 5 mL of methanol was slowly added (2 drops / s) to the system to quench the reaction; the solvent was then removed under reduced pressure, and the residue was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 10:1, v / v) to obtain compound I-2.
[0067] (4) Synthesis of monomer III: Under an argon atmosphere, 11-bromomethacrylate undecyl ester II (1.06 g, 3.32 mmol) was added to 80 mL of DMF, followed by potassium carbonate (0.41 g, 3.0 mmol) and compound I-2 (0.41 g, 3.0 mmol). The mixture was stirred at 85 °C under an argon atmosphere for 10 hours. After the reaction was completed, the solvent was removed from the resulting reaction solution, and the crude product was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 3:1, v / v) to obtain monomer III with a yield of 73%.
[0068] The characterization data of the obtained monomer III are as follows: 1 HNMR (400 MHz, CDCl3): δ 7.69 (dd, J = 9.6, 0.8 Hz, 1H), 7.10 (dd, J= 9.6, 2.1 Hz, 1H), 6.81 (d, J = 2.2 Hz, 1H), 6.09 (dd, J = 1.8, 1.0 Hz, 1H),5.54 (p, J = 1.7 Hz, 1H), 4.13 (t, J = 6.7 Hz, 2H), 4.04 (t, J = 6.5 Hz, 2H),1.94 (t, J = 1.3 Hz, 3H), 1.88-1.81 (m, 2H), 1.70-1.63 (m, 2H), 1.52-1.44 (m,2H), 1.39-1.28 (m, 12H); 13 CNMR (100 MHz, CDCl3): δ 167.51, 160.72, 150.16, 146.87, 136.52,129.66, 125.09, 117.04, 89.82, 68.85, 64.76, 29.43, 29.41, 29.24, 29.17,28.65, 28.55, 25.93, 25.91, 18.28; HRMS (ESI+) exact mass calculated for [M+Na] + (C 21 H 30 N2O4Na + ) requiresm / z 397.2098, found m / z 397.2096.
[0069] (5) Synthesis of self-healing sulfur bond material O-polymer: Monomer III (2.0 mmol) and DMF (2 mL) were mixed and ultrasonically treated to make them uniformly dispersed; the resulting solution was subjected to freezing-vacuuming-thawing cycle degassing, and the above degassing steps were repeated three times; after degassing, AIBN (0.05 mmol) was added to the above solution, and the reaction was stirred at 70 °C for 24 hours under nitrogen atmosphere; after the reaction was completed, the resulting reaction solution was naturally cooled to room temperature, 20 mL of water was added and stirred evenly, the resulting mixture was placed in a Teflon mold, and cured at 80 °C for 12 hours in a vacuum oven under nitrogen protection to obtain self-healing sulfur bond material O-polymer.
[0070] The characterization data of the obtained sulfur bond self-healing material O-polymer are as follows: 1 H NMR (400 MHz, CDCl3): δ 7.68 (t, J = 8.7 Hz, 1H), 7.15-7.02 (m,1H), 6.86-6.75 (m, 1H), 4.06-3.88 (m, 4H), 1.84 (q, J = 7.2 Hz, 3H), 1.60 (s,4H), 1.46 (t, J = 6.9 Hz, 2H), 1.33-1.26 (m, 13H), 0.87 (dp, J = 10.0, 6.0,4.4 Hz, 2H); SEC: Mn=38000g / mol; Mw=99000g / mol; Ð=2.61.
[0071] Experimental Example 1
[0072] Test 1: Self-healing test of the disulfide bond self-healing material prepared in Example 1 The sulfur bond self-healing material prepared in Example 1 was cut into test strips 6 mm wide × 18 mm long × 2 mm thick. These strips were then cut into two segments 6 mm wide × 9 mm long × 2 mm thick. The cut surfaces were brought into contact and allowed to heal in air at room temperature for 2 hours. The self-healing behavior of the Se-polymer was observed by manual stretching. The results are as follows: Figure 1 As shown, by Figure 1 It can be seen that the obtained self-healing material can completely heal in air for 2 hours, and the healed material has excellent tensile properties.
[0073] Test 2: Tensile properties of the self-healing disulfide bond materials prepared in Examples 1-2 The sulfur bond self-healing materials prepared in Examples 1-2 were cut into test strips with a width of 6 mm × a length of 22 mm × a thickness of 2 mm. Tensile tests were then performed along the length direction at room temperature (25°C) on an electronic universal testing machine (Instron 5943) at a speed of 10 mm / min. The test results are as follows: Figure 2 As shown, by Figure 2 It is known that the elongation at break of Se-polymer exceeds 10,000% and has measurable tensile strength; while after the introduction of covalent crosslinking, the tensile strength of CL-Se-polymer is significantly increased to 0.43 MPa, and the elongation at break decreases to about 600%.
[0074] Test 3: Tensile properties of the self-healing disulfide bond material prepared in Example 1. The self-healing sulfur bond material prepared in Example 1 was cut into three test strips, each 6 mm wide × 22 mm long × 2 mm thick. Two of these strips were then cut into two segments, each 6 mm wide × 11 mm long × 2 mm thick. The cut surfaces were allowed to heal for 2 hours in room temperature air and room temperature water, respectively. The healed samples were then subjected to tensile property testing according to the method described in Test 2. The results are as follows: Figure 3 As shown, by Figure 3 It is known that the material can achieve self-healing within 2 hours in both room temperature air and room temperature water environments. Using the elongation at break as the evaluation index, the mechanical properties of the healed sample can be fully restored.
Claims
1. A method for preparing a self-healing material with disulfide bonds, characterized in that, The steps include the following: (1) In solvent A, under the action of alkali, compound I is reacted with undecyl 11-bromomethacrylate II to obtain monomer III; In compounds of formula I and monomers of formula III, X is Se or O; (2) In solvent B, under the action of an initiator, monomer III and polyethylene glycol dimethacrylate undergo free radical polymerization to obtain a sulfur bond self-healing material.
2. The method for preparing the disulfide bond self-healing material according to claim 1, characterized in that, The solvent A mentioned in step (1) is N,N-dimethylformamide or toluene; the volume ratio of the solvent A to the molar number of the compound of formula I is 20-30 mL: 1 mmol; The base is potassium carbonate, potassium hydroxide, or sodium hydroxide, and the molar ratio of the base to the compound of formula I is 1-1.2:1; The molar ratio of 11-bromomethacrylate II to the compound of formula I is 1.05-1.2:1; The reaction temperature is 80-90℃, and the reaction time is 8-12h. The reaction is carried out under an argon atmosphere. After the reaction is completed, the post-processing steps of the resulting reaction solution are as follows: the solvent is removed from the resulting reaction solution, and the crude product is purified by silica gel column chromatography to obtain monomer III. The eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 3:
1.
3. The method for preparing the disulfide bond self-healing material according to claim 1, characterized in that, When X is Se in step (1), the compound of formula I has the structure shown in formula I-1: ; The compound shown in Formula I-1 was prepared by the following method: In solvent C, 4-amino-3-nitrophenol IV was hydrogenated under the catalysis of palladium on carbon to obtain 3,4-diaminophenol V; in solvent D, 3,4-diaminophenol V was subjected to an oxidative cyclization reaction with SeO2 to obtain compound I-1. 。 4. The method for preparing the disulfide bond self-healing material according to claim 3, characterized in that, In the preparation of the compound shown in Formula I-1, the solvent C is methanol, ethanol, or isopropanol; the volume ratio of the solvent C to the molar ratio of 4-amino-3-nitrophenol IV is 5-10 mL: 1 mmol; the mass fraction of palladium in the palladium-on-carbon catalyst is 10%, and the mass of the palladium-on-carbon catalyst is 5-15% of the mass of 4-amino-3-nitrophenol IV; the pressure of the hydrogenation reaction is 0.1-0.2 MPa, and the time of the hydrogenation reaction is 6-10 h; after the hydrogenation reaction is completed, the post-treatment steps of the resulting reaction solution are as follows: the resulting reaction solution is filtered through diatomaceous earth under an argon atmosphere, and the solvent is removed from the filtrate to obtain 3,4-diaminophenol V; The solvent D is ethanol or isopropanol; the volume ratio of solvent D to the molar ratio of 4-amino-3-nitrophenol IV is 5-15 mL:1 mmol; the molar ratio of SeO2 to 4-amino-3-nitrophenol IV is 1-1.05:1; the temperature of the oxidative cyclization reaction is 75-83℃, and the time of the oxidative cyclization reaction is 8-12 h; the oxidative cyclization reaction is carried out under an argon atmosphere; after the oxidative cyclization reaction is completed, the post-treatment steps of the obtained reaction solution are as follows: the solvent is removed from the obtained reaction solution, and the crude product is purified by silica gel column chromatography to obtain the compound shown in Formula I-1; the eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 2:
1.
5. The method for preparing the disulfide bond self-healing material according to claim 1, characterized in that, When X is O in step (1), the compound of formula I has the structure shown in formula I-2: ; The compound shown in Formula I-2 was prepared by the following method: (i) At 0-5°C, an aqueous solution of NaClO was added dropwise to an ethanol solution containing potassium hydroxide and 2-nitro-4-methoxyaniline VI to carry out an oxidative cyclization reaction to obtain compound VII; in solvent E, compound VII was reacted with triethyl phosphite to obtain compound VIII. (ii) At -35 to -30°C, BBr3 was added dropwise to a 1,2-dichloroethane solution of compound VIII, stirred until homogeneous, and then reacted to obtain the compound shown in formula I-2.
6. The method for preparing the disulfide bond self-healing material according to claim 5, characterized in that, In the preparation of the compound shown in Formula I-2, the mass fraction of the NaClO aqueous solution in step (i) is 5-10%; the molar ratio of NaClO to 2-nitro-4-methoxyaniline VI is 1.05-1.2:1; the molar ratio of potassium hydroxide to 2-nitro-4-methoxyaniline VI is 1.05-1.2:1; the concentration of 2-nitro-4-methoxyaniline VI in the ethanol solution containing potassium hydroxide and 2-nitro-4-methoxyaniline VI is 0.5-2 mmol / mL; the temperature of the oxidative cyclization reaction is 0-5℃, and the reaction time is 20-30 min; after the reaction is completed, the post-processing steps are as follows: the obtained reaction solution is filtered, the precipitate obtained by filtration is washed with water, and the solid obtained by washing is vacuum dried at 70-80℃ for 10-15 h to obtain the compound of Formula VII; The solvent E mentioned in step (i) is tetrahydrofuran; the volume ratio of the solvent E to the molar ratio of the compound of formula VII is 0.5-2 mL:1 mmol; the molar ratio of triethyl phosphite to the compound of formula VII is 2-2.2:1; the reaction temperature of the compound of formula VII with triethyl phosphite is 55-65℃, and the reaction time is 5-10 h; the reaction is carried out under a nitrogen atmosphere; after the reaction of the compound of formula VII with triethyl phosphite is completed, the post-treatment steps of the resulting reaction solution are as follows: the resulting reaction solution is naturally cooled to room temperature, diluted with water, and then the resulting mixture is extracted with n-hexane. The resulting organic phase is washed with saturated brine, dried with anhydrous MgSO4 to remove the solvent, and a crude product is obtained. The crude product is purified by silica gel column chromatography to obtain the compound of formula VIII. The eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 20:
1. Preferably, in step (ii), the molar ratio of BBr3 to compound VIII is 4-4.2:1; the concentration of compound VIII in the 1,2-dichloroethane solution of compound VIII is 0.1-0.3 mmol / L; the stirring temperature is -35~-30℃, and the stirring time is 20-30 min; the reaction temperature is 80-85℃, and the reaction time is 20-30 h; after the reaction is completed, the post-processing steps of the obtained reaction solution are as follows: the obtained reaction solution is cooled to -78℃, and methanol is added to quench the reaction; the solvent is removed from the obtained mixture, and the crude product is purified by silica gel column chromatography to obtain the compound shown in formula I-2. The eluent for silica gel column chromatography is a mixed solution of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate in the mixed solution is 10:
1.
7. The method for preparing the self-healing sulfur bond material according to claim 1, characterized in that, The solvent B mentioned in step (2) is N,N-dimethylformamide or toluene; the volume ratio of the solvent B to the molar number of monomer III is 0.5-1.5 mL: 1 mmol; The initiator is azobisisobutyronitrile or benzoyl peroxide; the molar ratio of the initiator to monomer III is 0.01-0.05:1; The number average molecular weight of the polyethylene glycol dimethacrylate is 200-400 g / mol; the molar ratio of the polyethylene glycol dimethacrylate to monomer III is 0-0.2:
1.
8. The method for preparing the disulfide bond self-healing material according to claim 1, characterized in that, The free radical polymerization reaction in step (2) is carried out at a temperature of 65-75°C for 20-30 hours; the free radical polymerization reaction is carried out under a nitrogen atmosphere. After the free radical polymerization reaction is completed, the post-processing steps are as follows: the obtained reaction mixture is naturally cooled to room temperature, water is added, and then cured at 70-80℃ for 10-15 hours under nitrogen protection to obtain a sulfur bond self-healing material; the ratio of the volume of water added to the molar number of monomer III is 8-12 mL: 1 mmol.
9. A self-healing material for disulfide bonds, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.
10. The application of the disulfide bond self-healing material according to claim 9 in the preparation of impact-resistant composite materials, biomedical implants, flexible electronic devices, and self-healing coatings.